2015
DOI: 10.5539/ijbm.v10n4p35
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Intention to Purchase Real Estate in Saudi Arabia: Moderating Effect of Demographic Citizenship

Abstract: Factors affecting the real estate market are of great importance worldwide. This study will investigate the factors influencing Saudis to purchase real estate. The study examine the effect of attitude, subjective norm, perceived behavior control and demographics on the intention to purchase real estate. Taking into account that demographics (Citizenship) as a moderator, a total of 450 questionnaires were distributed to respondents in Jeddah. Based on 322 questionnaires collected, the results show that there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Songkakoon et al (2014) believe that children and spouses are the main parties that will change their intention to buy home-related decisions in their Thai culture. Al-Nahdi et al (2015) also find that there is a positive impact between subjective norms on the intention to buy real estate in Jeddah and similar cases in Malaysia (MDRAZAK et al, 2013).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 81%
“…Songkakoon et al (2014) believe that children and spouses are the main parties that will change their intention to buy home-related decisions in their Thai culture. Al-Nahdi et al (2015) also find that there is a positive impact between subjective norms on the intention to buy real estate in Jeddah and similar cases in Malaysia (MDRAZAK et al, 2013).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 81%
“…Earlier research demonstrated the positive effect that subjective norms have on customer behaviour intentions (Tonglet et al , 2004; Al-Nahdi et al , 2015; Han and Kim, 2010). Our findings add to the literature by demonstrating that in the setting of the KSA telecom industry, subjective norms have a positive impact on switching and eWOM intentions.…”
Section: Results Conclusion and Future Researchmentioning
confidence: 98%
“…Latané (1981) In discussing subjective norms, various researchers regard them as the assumed pressure from society to or not to undertake a certain activity. Further, such research indicates that subjective norms have a significant effect on behavior (Ajzen, 1991;Al-Nahdi et al, 2015;Han and Kim, 2010;Kim and Han, 2009;Tonglet et al, 2004). Phungwong (2010) stated that customers' perceptions of social pressure had an impact on their purchase intentions and decisions.…”
Section: Subjective Normsmentioning
confidence: 99%
“…In this study the buying intention is measured with the help of three items Commitment to buy and recommendation status (CBA); Feel loyalty to buy (FLB); Buying an apartment will be wise decision (WDF). Many scholars have measured buying intention with the help of the aforesaid dimensions (Al-Nahdi, et al, 2015;Tan, 2013;Numraktrakul, et al, 2012;Phungwong, 2010;Houng, Chen andTsai, 2007).…”
Section: Buying Intention (Bi)mentioning
confidence: 99%